CURRENT VIEWS ON THE PROBLEMS AND DIAGNOSIS OF THE TREATMENT OF FEMALE INFERTILITY - Khomidova Shahlo Musinovna (Scholar Express Journals, 2022)
Infertility is a condition characterized by the inability to achieve a clinical pregnancy after 12 months of regular sexual activity without contraception due to impaired fertility, either individually or with his or her partner. Infertility interventions can be initiated even earlier than 1 year, based on medical, sexual and reproductive history, age, physical examination and diagnostic tests.
Keywords: Infertility; Obstetrics And Gynecology